2022
DOI: 10.1111/jan.15385
|View full text |Cite
|
Sign up to set email alerts
|

Empowering interventions for people living with dementia: A European survey

Abstract: Aims: We aim to identify existing empowerment interventions for people living with dementia and to explore which used interventions and projects are considered empowering and why. Design: This was an online survey. Methods: We conducted an online survey between May 2018 and July 2018 amongst professionals interested in dementia care in Europe. Interventions were clustered within the ecological model for health promotion. Reasons from respondents as to why they considered interventions to be empowering were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Moreover, an extensive systematic literature review showed that empowerment is a dynamic process, with it taking place within the interaction of the person living with dementia and their environment ( van Corven et al, 2021b ). The European survey showed that stakeholders considered a broad range of interventions empowering in dementia care and research ( van Corven et al, 2022 ). However, none of the available interventions in this survey were specifically developed for or aimed at empowerment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, an extensive systematic literature review showed that empowerment is a dynamic process, with it taking place within the interaction of the person living with dementia and their environment ( van Corven et al, 2021b ). The European survey showed that stakeholders considered a broad range of interventions empowering in dementia care and research ( van Corven et al, 2022 ). However, none of the available interventions in this survey were specifically developed for or aimed at empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 1 of the MRC framework: Intervention development. Between May 2018 and November 2020, we performed a needs assessment, using focus group discussions and interviews with stakeholders (van Corven et al, 2021a), an integrative literature review (van Corven et al, 2021b), and a European survey to identify existing empowerment interventions (van Corven et al, 2022). Between April and December 2019, regular meetings were held with the project team to discuss and interpret the results of the needs assessment, determine program objectives, and select behaviour change techniques that could be applied in nursing homes.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the PwD in this study expressed similar views on usefulness and empowerment to those described in other studies by elderly people and centenarians without dementia [ 3 , 22 , 23 ], clearly emphasizing the importance of sustaining social contacts and providing the possibility of interacting with the environment for PwD and old people in general. Recently, concepts for supporting PwD have undergone a shift from task-oriented support to a person-centered approach, explicitly focusing on strengthening personal competencies, decision-making and self-worth, reframing the dementia diagnosis from one of ‘disabled’ to ‘enabled’ [ 24 , 25 , 26 , 27 ]. The European research group (INTERDEM) explicitly emphasizes that psychosocial interventions should focus on promoting the autonomy, dignity and rights of PwD, and communities should make themselves available to PwD from early diagnosis onwards [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The European research group (INTERDEM) explicitly emphasizes that psychosocial interventions should focus on promoting the autonomy, dignity and rights of PwD, and communities should make themselves available to PwD from early diagnosis onwards [ 28 , 29 , 30 ]. However, the process is very slow, as a recent survey revealed for Europe [ 26 ]. The challenge of an increased life expectancy at birth and a demographic shift towards older age also necessitates programmes that promote healthy ageing in the population, as well as programmes that support PwD as one of the major medical concerns in old age.…”
Section: Discussionmentioning
confidence: 99%